Identification and distribution of whiteflies (Hemiptera: Aleyrodidae) in tomato crops (Solanum lycopersicum) in Cundinamarca (Colombia) - Ángel D., Jorge E.; Martínez H., Julián; Santamaria G., Maikol; Parada P., Sandra; Ebratt R., Everth (Instituto Colombiano Agropecuario - ICA, 2025)
The main purpose of this study was to determine the presence, distribution and characterization of whiteflies in thirteen tomato-crop producing municipalities in Cundinamarca (Colombia). Immature stages were collected and taken to the laboratory until adults emerged in order to establish their taxonomic identification. The mitochondrial regions were amplified with specific primers, which allowed for the allocation of biotypes in Bemisia tabaci. Genetic similarity analysis was performed in Trialeurodes vaporariorum using RAPD and phylogenetic analysis of the gene sequences mtCOI. The presence of T. vapo- rariorum was established in 100% of the municipalities visited and B. tabaci biotype B was detected in 32%, coexisting with T. vaporariorum. A wide distribution of T. vaporariorum was determined between 653 and 2,680 m a.s.l. B. tabaci was found between 653 and 1,940 m a.s.l distributed in four municipalities in the Sumapaz, lower Magdalena, and Rio Negro provinces. The RAPD analysis established high genetic similarity between the T. vaporariorum insects. The phylogenetic analysis did not allow for the resolution of structured groups inside the analyzed T. vaporariorum samples.